Anticipating WPS PIN Vulnerability to Secure Wireless Network - Rianto, Indra Dwi (ComTech: Computer, Mathematics and Engineering Applications, 2013)
WiFi Protected Setup (WPS) is a standardized function supported by numerous vendors of wireless routers and access point to help set up connection to a wireless local area network. It is designed to simplify the set up and generally enabled by default. Due to design flaw, the WPS or QSS PIN is susceptible to a brute forceattack. In this paper, we test the security vulnerability occurred, evaluate the performance and give recommendations to anticipate the attack.